Carcass characteristics and meat quality of broilers fed with crude glycerin originated from palm oil and wasted vegetable oil in diets - Astiari Tia Legawa; Chaiyawan Wattanachant; Sutha Wattanasit (Acta Scientiarum. Animal Sciences, 2018)
A study was conducted to evaluate the effect of crude glycerin on slaughter weight and carcass characteristics of broilers. Total of 180 male Ross - 308 day old chicks were allocated to 3 treatments with 4 replicates in a completely randomized design. The dietary treatments were: diet without crude glycerin inclusion (T1), diet with 5% crude glycerin inclusion from waste vegetable oil (T2), and diet with 5% crude glycerin inclusion from palm oil (T3). On day 42, twenty chickens per treatment were randomly sampled and slaughtered to determine the carcass characteristics. From the study, both crude glycerins did not give any effect on the slaughter weight and carcass characteristics, but broilers received crude glycerin had higher abdominal fat (p < 0.001) than control. Drip loss, cooking loss, pH, and meat color were not influenced by both types of crude glycerin, however, the skin color was significantly affected by palm oil crude glycerin inclusion (p < 0.05). Furthermore, meat from broilers with crude glycerin had higher lipid oxidation than control (p < 0.001). In conclusion, crude glycerins could be added in broiler’s diet, however its effect on increasing fat and lipid oxidation must be taken into concern.